LEGAL PROTECTION FOR WORKERS AT LKP SAHABAT CENDEKIA SIGLI, INDONESIA - Rahmatillah, Muhammad Syaukas; Edi Yuhermansyah (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2024)
The Institute of Courses and Education or LKP is one form of non-formal education institution that employs educators as applicable in formal education. However, in some LKP cases, it raises problems including the absence of contractual provisions of employment agreements that cause uncertainty and protection for both parties between LKP and workers. For this reason, the focus of this research is how is the system and form of employment contract and its implementation at LKP Sahabat Cendekia Sigli, and how is the legal protection for workers at LKP Sahabat Cendekia Sigli reviewed according to the ijārah ‘alā al-’amal contract? This research is studied with a conceptua lapproach approach with the type of empirical legal research. The result of the research is that the system and form of employment contract between workers and LKP Sahabat Cendekia Sigli is in the form of an oral agreement with the provision that the manager explains the amount of salary/wages per hour and subject, as well as teaching hours or days. The LKP does not explain the expiration date of the contract. In the context of protection and legal certainty, the status of workers in the LKP and the LKP itself does not have legal certainty. On the one hand, there is uncertainty and legal protection for the LKP because workers can decide to resign/leavethe LKP. On the other hand, workers also do not get legal certainty and protection because the LKP can also terminate the employment contract at any time. For this reason, seen from the ijārah ‘ala al-’amal contract, the implementation of the employment contract at the Sahabat Cendekia Sigli LKP is not in accordance with the principles of sharia contracts. The ijārah alā al-'amal contract requires the certainty of a written agreement contract and the actions of the two parties are bound by and limited by the agreed agreement letter. This is what is missing in the work agreement at LKP Sahabat Cendekia Sigli.